Effect of weed management methods and plant spacing on the growth and yield of cassava morphotypes (Agriculture, Food, and Natural Resources Journal, 2026)
An integrated weed management system comprising crop spacing, cassava variety, and different weed control methods in the control of M. invisa in cassava farms was done at Umudike, Southeastern Nigeria, for two cropping seasons. This was conducted in two seasons under a split-split-plot design within a randomized complete block design, replicated three times. The main plot treatments consisted of three crop spacings [1m x 0.6m (S1), 1m x 0.8m (S2), and 1m x 1m (S3)]. Two cassava varieties with contrasting morphologies—sparse branching TME 419 (V1) and profuse branching NR 8082 (V2)—were used as subplot treatments. The sub-sub-plot treatments included four weed control methods: hoe weeding at 4, 8 & 12 WAP [weeks after planting (W1)]; application of pre-emergence herbicide (Primextra G. 660 sc at rate 2.5 kg a.i./ha) 1 DAP + hand weeding at 12 and 16 WAP (W2); application of pre-emergence herbicide (Primextra G. 660 sc at rate 2.5 kg a.i./ha) 1 DAP + post-emergence herbicide (Envoke at rate 7 g a.i./ha) at 8 WAP (W3); and control [weedy plot (W0)]. The collected data were analyzed using analysis of variance (ANOVA),
Keywords: Plant spacing; Primextra; Residue management; Weed control